TERMOGRAVIMETRI ANALISIS ULTIMAT DAN PROKSIMAT BIOMASSA SERTA PENENTUAN NILAI KALOR - Rifqi Sufra; Herri Susanto; Jenny Rizkiana; Suharto Suharto; Arysca Wisnu Satria (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2026)
Biomass characterisation is important for knowing the contained components in biomass. Some types of biomass studied were wood of acacia (Acacia mangium), gamal (Gliricidia sepium), coconut shell (Cocos nucifera) charcoal, and wood charcoal, for the gasification process through proximate analysis, ultimate analysis, and determination of high heating value (HHV). Ultimate analysis data utilised thermogravimetric analysis (TGA) for efficiency. The characterisation results show that coconut shell charcoal and wood charcoal have the highest fixed carbon content (72.66% and 68.98%) and higher C element (57.87% and 54.94%) as well as lower ash content compared to acacia wood and gamal wood, resulting in the highest calorific value (30.01 and 22.05 mJ/kg) and potentially better gasification performance. Conversely, acacia wood and gamal wood show relatively higher volatile matter content (64.03% and 76.38%) and ash (18.88%), resulting in lower calorific values. Overall, the research results indicate that coconut shell charcoal and wood charcoal are more recommended as the primary fuel in the gasification system.